Psychometric evaluation and updated community norms of the WHO-5 well-being index, based on a representative German sample - Sören Kliem; Anna Lohmann; Sebastian Fischer; Dirk Baier; Dirk Baier; Vera Clemens; Cedric Sachser; Hanna Kampling; Elmar Brähler; Elmar Brähler; Jörg M. Fegert (Frontiers in Psychology)
IntroductionThe World Health Organization-Five Well-Being Index (WHO-5) is a widely used self-report measure for evaluating mental well-being in both general and clinical populations. This study examines the psychometric properties of the WHO-5 using a large, representative sample of the adult population in Germany (N = 2,515) and presents updated population norms.MethodsAnalyses included item-level statistics such as means, standard deviations, and inter-item correlations. Construct validity was evaluated through correlations with measures of depression (PHQ-2), anxiety (GAD-2), somatic symptoms (SSS-8), and loneliness (UCLA Loneliness Scale). Internal consistency was measured using coefficient omega, while factorial validity was tested through confirmatory factor analysis based on a one-factor model. Measurement invariance was assessed across gender and age groups using multi-group confirmatory factor analyses. Population norms are reported for the total sample and various age groups.ResultsThe findings confirm the strong psychometric properties of the WHO-5, including its internal consistency and construct validity. Measurement invariance results support comparability of scores across gender and age. The updated norms offer.DiscussionThese updated norms support the continued implementation of the WHO-5 as a practical tool for population-based prevention and mental health care planning.